Elaboração de um banco de dados de gerenciamento de resíduos da construção civil: estudo de caso na rede hoteleira de Gramado/RS - Neumann, Morgana (My University, 2022)
The accelerated demographic growth, the increase of the purchasing power of the population and the cities development, contribute to the building sector being responsible for a big part of impacts caused in the environment. In addition to consuming non-renewable energy and natural resources, it alters the landscape and generates a large volume of waste, a reflection of inefficient management. The objective of the work is to elaborate a civil construction waste management database, targeted do entrepreneurs and environmental consultants, to the Hotel Chain from Gramado/RS. The data were collected in four different hotel enterprises, which are in construction, located in Gramado/RS, through the filling of a check list. The information about the waste have been detected by the Cargo Manifest of Waste provided by the Companies, and so being posted in an Excel spreadsheet. As results, the generation quantitative data (total of 760.1718 t and 747.3 m³) shows that the waste from type B was the most expressive (726.2648 t e 460.4 m³), corresponding to 95.53% and 61.60% of the waste generation, respectively and classified (11 of 23 kinds). Related to the storage and packaging, the waste from type A are placed in the soil, the waste from type B and C in stalls, bags or boxes that are covered and identified by color and type, and the ones from type D, according to technical standards. The results provide subsidies to a sustainable management of the waste to the entrepreneurs and environmental managers with data close to reality for the preparation of Waste Management Plans. The efficient management depends on right activities in the building site, looking not only for profits with the waste, but also the reduction of costs of the destination ant treatment, trough the reuse and recycling, projecting always the social, environmental and economic axis of sustainability. [resumo fornecido pelo autor]
O acelerado crescimento demográfico, o aumento no poder aquisitivo da população e o desenvolvimento das cidades, contribuem para que o setor da construção seja responsável por grande parte dos impactos causados ao meio ambiente. Além de consumir energia e recursos naturais não renováveis, altera a paisagem e gera grande volume de resíduos, reflexos de um gerenciamento ineficiente. O objetivo do trabalho é elaborar um banco de dados de gerenciamento de resíduos da construção civil para a rede hoteleira de Gramado/RS, direcionado aos empreendedores e consultores ambientais. Os dados necessários para o banco de dados foram coletados em 04 empreendimentos hoteleiros em construção localizados em Gramado/RS, por meio do preenchimento de um checklist in loco. As informações sobre os resíduos gerados foram retiradas dos Manifestos de Transporte de Resíduos fornecidos pelas empresas e planilhados no Excel. Como resultados, os dados quantitativos de geração (total de 760,1718 t e 747,3 m³) e qualitativos de classificação dos resíduos demonstram que os resíduos Classe B foram os mais expressivos (726,2648 t e 460,4 m³), correspondendo a 95,53% e 61,60% da geração respectivamente, e classificação (11 de 23 resíduos). Quanto ao armazenamento e acondicionamento, os resíduos classe A são dispostos no solo, os Classe B e C em baias, bags e ou caixas com cobertura e identificados por cor e tipo e os Classe D conforme normas técnicas. Os resultados fornecem aos empreendedores subsídios para o gerenciamento sustentável dos resíduos e aos gestores ambientais dados próximos à realidade para a elaboração dos Planos de Gerenciamento de Resíduos. O eficiente gerenciamento do resíduo depende de corretas ações no canteiro de obras, visando não somente o ganho com o resíduo, mas também a redução de custos de destinação e tratamento através da reutilização e reciclagem, projetando sempre os eixos social, ambiental e econômico da sustentabilidade. [resumo fornecido pelo autor]
Keywords: Construção civil - Eliminação de resíduos; Banco de dados; Hotéis - Gramado (RS); Building - Waste disposal; Databases; Hotels - Gramado (Brazil)